A CONTRASTIVE STUDY OF THE STRUCTURAL AND FUNCTIONAL CHARACTERISTICS OF NOMINAL GROUPS IN ENGLISH AND YORUBA FOR EFFECTIVE LANGUAGE TEACHING - DAHUNSI, Toyese Najeem; SAJO, Muhammad Aliyu; DYAKO, Leo Aondonguter (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
English L1 speakers learning Yoruba L2 and vice-versa keep increasing globally. Language learning involves difficulties that arise from transfer of L1 features to L2, hence the need for a contrastive understanding of both languages. This work is a contrastive approach to the understanding of the structure of both English and Yoruba nominal groups (NGs) aimed at identifying structural and functional similarities and peculiarities. Eight hundred NGs (400 from each language) were randomly sampled from selected English and Yoruba newspapers. The analysis was based on the ideational metafunction of the systemic functional grammar, broken into the experiential and logical sub-types. This involved, first, a multivariate categorisation of the constituents of each NG into Deictic, Numerative, Epithet, Classifier, Thing, and Qualifier; and second, a univariate categorisation that accounted for instances of constituents that have iterations of the same functional relationships. The results of analyses led to some findings. One, both languages have similar functional elements, and each functional element has similar constituents in both languages. Two, while English has more functional elements in the premodification block but less in the postmodification block, Yoruba has less in the premodification block but more in the postmodification block. Three, the deictic and epithet are functionally and positionally fixed in English NGs whereas they are functionally split and positionally flexible in Yoruba NGs. Lastly, the variation in element ordering results in more structural peculiarities than similarities in both languages. Teachers’ adequate familiarisation with the characterising similarities and peculiarities of the structure of NGs in both languages will facilitate an effective teaching of both languages.